The Effect of Profitability, Leverage, Company Size, and Inventory Intensity on Tax Avoidance (A Study of Health Sector Companies Listed on the IDX in the 2021–2024 Period) - Melyyana Eka Putri Suwanda; Eni Srihastui; Moch. Wahyudi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Indonesia’s healthcare sector experienced substantial post-pandemic growth, with revenues increasing by 11.7% in 2024. However, strict regulatory oversight by the Food and Drug Supervisory Agency (BPOM) and high inventory intensity create unique dynamics in corporate tax avoidance behavior. This study examines the effect of profitability (Return on Assets/ROA), leverage (Debt to Equity Ratio/DER), company size (SIZE), and inventory intensity (INV) on tax avoidance, operationalized as using the Effective Tax Rate (ETR), in healthcare companies operating in the sector and listed on the Indonesia Stock Exchange (IDX) over the 2021–2024 period. Grounded in agency theory and the political cost hypothesis, this this study adopts a quantitative methodology utilizing secondary data derived from annual financial reports. A total of 56 firm-year observations from 14 companies were selected through purposive sampling. Panel data regression analysis was conducted using EViews 13, including model the analysis involves panel data model selection tests (Chow, Hausman, and Lagrange Multiplier), classical assumption testing, and hypothesis testing through t-tests and F-tests. The results indicate that profitability (β = −0.0047; p = 0.0018) and inventory intensity (β = −0.2142; p = 0.0234) exert a significant negative influence on tax avoidance, whereas leverage and firm size exhibit no statistically significant impact. Simultaneously, the independent variables explain 32.61% of the variation in tax avoidance (R² = 0.3261; p = 0.0004). These findings support the political cost hypothesis.